Identidad Cultural y Patrimonio Alimentario de la parroquia Santiago de Guanando, cantón Guano, Provincia de Chimborazo - Ramos Lema, Alisson Vanessa (2024)
The research titled "Cultural Identity and Food Heritage of the Santiago de Guanando Parish, Guano Canton, Chimborazo Province" aims to analyze the relationship between cultural identity and food heritage in the Santiago de Guanando parish. This study was conducted using fieldwork, exploratory research, and documentary analysis, which provided significant data for the investigation. Deductive, inductive, and correlational methods were applied. Surveys were administered to both the inhabitants of the parish and officials of the Guanando Parish GAD, using a set of indicators and 9 questions on a Likert scale. The reliability of the instruments was verified using the SPSS software, and the survey results were analyzed through tables and graphs, culminating in hypothesis testing. Based on the findings, conclusions and recommendations were formulated, including a proposal called "Guanando Vive!" aimed at creating a web portal to offer detailed information about the parish's cultural and heritage identity. The goal is to promote a significant tourism initiative that encourages the local population to preserve and celebrate their customs and traditions.